Helicobacter Pylori Infection in Sjögren’s Syndrome: Co-incidence or Causality? - Saghafi, Massoud; Abdolahi, Nafiseh; Orang, Reza; Hatef, Mohammad R.; Molseghi, Mohammad Hadi (Current Rheumatology Reviews, 2019)
Background and Aim: Lymphoid cell infiltration and destruction of exocrine glands, specifically lacrimal and salivary glands are characteristics of Sjogren’s syndrome (SS). An etiological role has been proposed for Helicobacter pylori (H. pylori), interacting in the clinical course and complications of SS (including gastric cancer and lymphoma). The aim of this study was to identify the probable correlation between H. pylori infection and Sjogren’s syndrome (SS). Methods: In this case-control study, ELISA method was used to determine serum level of IgA and IgM anti H. pylori antibody in 43 subjects with SS according to the international criteria and 95 healthy subjects as control. SPSS-17 was used to analyze data with t-test. P value <0.05 were considered significant. Results: Serum level of IgM (34.9% vs. 10.5%, p-value= 0.001) and IgA (67.4% vs. 46.3% p value= 0.021) anti H. pylori antibody were significantly higher in SS patients compared to the control group. There was a positive correlation between age and H. pylori infection (r=0.2, Pvalue= 0.05). Conclusion: Patients with SS had a higher prevalence of H. pylori infection compared to the normal population. Eradication of H. pylori is recommended particularly in older patients with SS.
Keywords: H. pylori